Impact of climatic variabilities and extreme incidences on the physical environment, public health, and people’s livelihoods in Ethiopia - Teku, Degfie; Eshetu, Sintayehu (Frontiers in Climate, 2024)
Ethiopia’s vulnerability to climate change is exacerbated by high poverty rates, rapid population growth, increasing prevalence of vector-borne diseases, and heavy reliance on rain-fed agriculture. This narrative review aims to compile existing data on the impacts of climate extremes on the physical environment, public health, and livelihoods in Ethiopia, thereby highlighting the significance of this region for such a study. Data were sourced from peer-reviewed journal articles from databases like PubMed, Scopus, and Web of Science, as well as reports and other unpublished documents. Results show that Ethiopia is facing increasing frequency, severity, duration, and timing of climate-related extreme events. Key challenges include environmental degradation, reduced crop yields, recurring floods, droughts, famines, increased heat waves, and spread of infectious diseases. Average daily rainfall is projected to decrease from 2.04 mm (1961–1990) to 1.97 mm (2070–2099), indicating a worsening climate trend. Moreover, the average annual temperature has risen by 1.3°C since 1960, at a rate of 0.28°C per decade. Flood records indicate a sharp rise, with 274 flood incidents recorded in 2020, causing extensive damage, including an annual soil loss of 1 billion tons in the Ethiopian highlands, reducing land productivity by 2.2% annually. Droughts from 1964 to 2023 affected 96.5 million people, reduced GDP by 4%, decreased agricultural output by 12%, and increased inflation rates by 15%. The regions of Afar, Somali, Gambella, and Benshangul Gumuz exhibit extreme vulnerability to health impacts due to rising temperatures. Addressing climate extremes is critical to mitigate their adverse effects on Ethiopia’s environment, public health, and livelihoods.